Motivation And Involvement Toward Physical Activity Among University Students - Abdullah, Mohd Firdaus; Md Yusof, M. K.; Nazarudin, M. N.; Abdullah, M. R.; Maliki, A. B. H. M. (J Fundam Appl Sci., 2018)
This study investigates intrinsic and extrinsic factors that influence involvement of university students to participate in physical activity. 400 students comprising 200 men and 200 women were used as the main respondents were respond to the adapted Exercise Motivations Inventory questionnaire. It revealed that highest mean value of the intrinsic factors are health and fitness (M = 4.37), while for extrinsic factors are factors peers and friends (M = 3.97). There is significant differences in the involvement of intrinsic motivation factors motivated health and fitness (t = -5.05, p < 0.05) and body-related factors (t = -6.51, p < 0.05) by gender. As for the extrinsic motivation that only the family (t = -6.98, p < 0.05) showed significant differences by gender. Lastly, intrinsic motivation body related and extrinsic motivation factors (role of university) are the most contributing factors to the physical activity.